CLIMATE CHANGE IN UZBEKISTAN AND ITS IMPACT ON WATER RESOURCES (Ustozlar uchun, 2026)
This article examines the impact of climate change on water resources in Uzbekistan. The study highlights the trends of temperature and precipitation changes, the reduction of river flow, and groundwater depletion. The article also discusses the implications of climate change for agriculture, urban water supply, and sustainable development in the region. Methodological approaches including literature review, statistical analysis of climatic and hydrological data, GIS mapping, and expert interviews were applied. The results demonstrate that Uzbekistan’s water resources are increasingly under pressure due to rising temperatures, changing precipitation patterns, and human activities. The study emphasizes the urgent need for integrated water resource management, adaptation strategies, and sustainable policies to mitigate the negative effects of climate change.